Influence de la Longueur de Grille sur les Impédances d’entrée et de sortie du Transistor Mesfet GaAs, ISSN 1112-9697 - Benbouza Med Salah; F. Z .Maalla; I. Sellaoui (Revue des Sciences et de la Technologie, 2014)
In information science such as computer, telecommunications, processing of the transmission of signals or images, the components field effect plays a role. Also we are interested in our study to field-effect transistor gate Schottky micron and submicron in gallium arsenide GaAs MESFET said. In this paper, we present the results of calculating the influence of gate length on input impedance and output transistor field effect Schottky barrier gallium arsenide GaAs MESFET said, this physical model is based on the analysis of two-dimensional Poisson equation in the active region under the gate. The theoretical simulation results based on analytical expressions that we have established above, are discussed and compared with those of the experiment